Enzymatic Tandem Approach to Knoevenagel Condensation of Acetaldehyde with Acidic Methylene Compounds in Organic Media. Issue 31 (21st August 2017) - Koszelewski, Dominik; Paprocki, Daniel; Madej, Arleta; Borys, Filip; Brodzka, Anna; Ostaszewski, Ryszard
Abstract : A tandem enzyme‐catalyzed Knoevenagel reaction with acetaldehyde is presented. A new protocol for the synthesis of the desired products through a tandem process based on the enzymatic hydrolysis and Knoevenagel reaction starting from acetaldehyde precursors is disclosed. The influence of the reaction conditions including organic solvent, enzyme type, and temperature on the reaction course was tested. Further, this protocol was extended by subsequent tandem chemoenzymatic transformations leading to epoxides. Abstract : The first example of an enzyme‐catalyzed Knoevenagel reaction on an aliphatic aldehyde (acetaldehyde) providing unsaturated products in water‐free organic solvents his described. The new protocol for the synthesis of the desired products through a tandem process based on enzymatic hydrolysis of esters and Knoevenagel reaction starting from acetaldehyde precursors (vinyl carboxylates) is disclosed.